Teacher's Perception Of The Contributions Of Oil Exploration To Educational Development In Oguta L.G.A. - Charles, Ekwe Chiwundu; Ngozi-Ohehi, L. C. (Advances in Social Sciences Research Journal, 2018)
This study examined: Teachers Perception of the contributions of Oil Exploration on the Development of Education in Oguta Local Government Area of Imo State. Two research questions were developed and one null hypothesis was formulated. The design of the study was the population survey design. All the 80 teachers in Imo State Government owned schools were involved in the research. A 20 item researcher developed structured questionnaire was the instrument for data collection. Content validity was established for the questionnaire while the Cronbach alpha was used to establish its reliability. Data for answering the research questions were analyzed using mean score. The analysis of data for the null hypothesis was carried out with the t-test for independent samples and tested at 0.05 level of significance. The two research questions were answered in the negative. The null hypothesis was accepted and the findings showed that there is no relationship between the contributions of oil exploration and educational development in Oguta Local Government Area. The observational findings showed that the schools located in Oguta Local Government Area where in a state of abandonment. Among others researcher recommended that the Multinational Oil Companies bear the responsibilities of employing teachers who will teach in partner with teachers recruited by government in public schools located in Oguta Local Government Area. The educational implications of the findings were discussed. Suggestions for further studies were also put forward.